Threshold Effects of Financial Stress on the Relationship Between Oil Price Volatility and the COVID-19 Crisis on Stock Return Volatility in Pharmaceutical Companies Listed on the Tehran Stock Exchange - Ehtemami, Negar; Agheli, Lotf Ali; Peykarjou, Kambiz (Business, Marketing, and Finance Open, 2026)
The present study aims to investigate the threshold effects of financial stress on the relationship between oil price shocks and the COVID-19 crisis on stock return volatility in pharmaceutical companies listed on the Tehran Stock Exchange. This study is applied in purpose and descriptive-analytical in nature, using an ex post facto design and panel data covering the period 2013–2024. The financial stress index (FSI) is constructed using Principal Component Analysis (PCA) based on nine macro-financial indicators across governmental, monetary, and exchange-rate sectors. Oil price shocks are extracted using the Exponential Generalized Autoregressive Conditional Heteroskedasticity (EGARCH) model to capture asymmetric volatility effects, while stock return volatility is estimated through ARMA-EGARCH modeling after confirming conditional heteroskedasticity using the ARCH test. The COVID-19 crisis is incorporated as a dummy variable. To analyze nonlinear relationships and regime-switching behavior, the Panel Smooth Transition Regression (PSTR) model with a logistic transition function is employed, where financial stress serves as the transition variable. Model validity is assessed through unit root tests (LLC), cointegration tests (Kao), linearity tests, and diagnostic checks for autocorrelation and heteroskedasticity. The results indicate that financial stress, COVID-19, oil price shocks, and inflation all have positive and statistically significant effects on stock return volatility. The linearity hypothesis is rejected, confirming the presence of nonlinear dynamics and regime-dependent relationships. The estimated threshold value of financial stress is significant, and the slope parameter indicates a relatively rapid transition between regimes. In the high financial stress regime, the effects of all explanatory variables intensify substantially, with financial stress showing the largest marginal impact on volatility. Oil price shocks exhibit asymmetric effects, with positive shocks generating greater volatility than negative shocks. The COVID-19 crisis significantly increases volatility, particularly under high financial stress conditions. Diagnostic tests confirm model adequacy, stability of parameters, and absence of econometric violations. The findings demonstrate that stock return volatility in pharmaceutical companies is driven by a nonlinear interaction of macroeconomic shocks and financial conditions, where financial stress acts as a critical threshold variable amplifying the effects of oil price volatility, inflation, and the COVID-19 crisis.